URGENSI PENDIDIKAN AKHLAK DI SEKOLAH - Hasnul Yakin; Warnis Warnis (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
Understanding morals can be seen one of them in the Big Indonesian Dictionary (KBBI), namely: nature, behavior. In a hadith, that good is broadly noble character. The urgency of morality in the personality of a student and in life is that he will elevate the person's degree to a high position with a noble character, on the contrary bad character will demean someone, even though he or she is a respected person in the midst of society. In the article, the author tries to explain the urgency of morality and the importance of moral education in schools. In education today, the cultivation of three main points of Islamic teachings is very important, namely faith, worship and morals. Moral as one of them. In this article, the writer uses the maudhu 'method, collects verses with the same theme and is perfected with several traditions, then concluded. According to the author, it is very important to teach moral lessons to students at school again and to practice them directly.